How the COVID-19 pandemic is affecting the 17 Sustainable Development Goals - Rocha, Cézar Henrique Barra; Gorne, Íris Batista; Romualdo, Sanderson dos Santos (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
The Sustainable Development Goals (SDG) set universal goals and suggest ways to help achieve social security, mitigate gender, racial and economic inequalities, and protect the environment and biodiversity. However, the current COVID-19 pandemic has made the achievement of these goals more distant and has impacted the development of the social, economic and environmental spheres, including the SDG. Therefore, the purpose of this article was to discuss how the COVID-19 pandemic is affecting the 2030 Agenda and its 17 SDG. It was developed using a methodology based on systematic literature review, through the consultation of digital libraries and publications on official websites. To achieve its objectives, the text is structured in topics with the 17 SDG and their respective impacts. The authors observed an increase in structural inequities in several spheres, such as health, education, housing, security, and food, with socioeconomically vulnerable populations being the most affected. With regard to the environment, there were improvements in the quality of air and water courses, however, there was an increase in the deposition of plastic in the oceans and in landfills due to the use of disposable personal protective equipment (PPE) by the global population. Furthermore, due to the approaching global depression, together with insufficient political and economic attention, it becomes uncertain and unlikely that the SDG will be achieved in 2030. It is concluded that there is a need for an integrated action between public policy makers, social actors and the private sector, so that they can give an effective response towards a single objective: the improvement of the quality of life of Planet Earth and of all beings that live in it.